The North Atlantic oscillations: cycle times for the NAO, the AMO and the AMOC - Seip, Knut Lehre; Grøn, Øyvind; Wang, Hui (Climate, 2019)
We show that oceanic cycle lengths persist across oceanic cyclic time-series by comparing cycles in series that come from “sister” measurements in the North Atlantic Ocean. These are the North Atlantic oscillation (NAO), the Atlantic multidecadal oscillation (AMO) and the Atlantic meridional overturning circulation (AMOC). The raw NAO series, which is an extremely noisy series in its raw format, showed cycles at 7, 13, 20, 26 and 34 years that were common with or overlapped the other two series and across increasing degrees of smoothing of the NAO series. At the 1960 midpoint of the hiatus period 1943- 1975, NAO was leading time series to AMOC and AMO and AMO was a leading time series to AMOC, but in 1975, at the end of the hiatus period, the leading relations were reversed. This research received no external funding apart from support from Oslo Metropolitan University. publishedVersion